RESPIRATORY DISTRESS SYNDROME IN INFANTS- AN OVERVIEW - Vijaya Kumaran, Ghayathri; Sethu, Gowri; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Respiratory distress syndrome (RDS) is a breathing disorder that affects newborns. RDS rarely occurs in full-term infants. The disorder is more common in premature infants born about 6 weeks or more before their due dates. In fact, nearly all infants born before 28 weeks of pregnancy develop RDS. RDS is more common in premature infants because their lungs aren't able to make enough surfactant (sur-FAK-tant). A surfactant is a liquid that coats the inside of the lungs. It helps keep them open so that infants can breathe in air once they're born. Without enough surfactant, the lungs collapse, and the infant has to work hard to breathe. He or she might not be able to breathe in enough oxygen to support the body's organs. The lack of oxygen can damage the baby's brain and other organs if proper treatment isn't given. Most babies who develop RDS show signs of breathing problems and a lack of oxygen at birth or within the first few hours that follow. Due to improved treatments and medical advances, most infants who have RDS survive. However, these babies may need extra medical care after going home. Some babies have complications from RDS or its treatments. Serious complications include chronic (ongoing) breathing problems, such as asthma and BPD; blindness; and brain damage. This paper will outline the clinical course and diagnosis and treatment for the same and also will draw a simple conclusion.